Pathogenic variants in nucleoporin TPR (translocated promoter region, nuclear basket protein) cause severe intellectual disability in humans. Issue 3 (7th September 2021) - Van Bergen, Nicole J; Bell, Katrina M; Carey, Kirsty; Gear, Russell; Massey, Sean; Murrell, Edward K; Gallacher, Lyndon; Pope, Kate; Lockhart, Paul J; Kornberg, Andrew; Pais, Lynn; Walkiewicz, Marzena; et al.
Abstract: The nuclear pore complex (NPC) is a multi-protein complex that regulates the trafficking of macromolecules between the nucleus and cytoplasm. Genetic variants in components of the NPC have been shown to cause a range of neurological disorders, including intellectual disability and microcephaly. Translocated promoter region, nuclear basket protein (TPR) is a critical scaffolding element of the nuclear facing interior of the NPC. Here, we present two siblings with biallelic variants in TPR who present with a phenotype of microcephaly, ataxia and severe intellectual disability. The variants result in a premature truncation variant, and a splice variant leading to a 12-amino acid deletion respectively. Functional analyses in patient fibroblasts demonstrate significantly reduced TPR levels, and decreased TPR-containing NPC density. A compensatory increase in total NPC levels was observed, and decreased global RNA intensity in the nucleus. The discovery of variants that partly disable TPR function provide valuable insight into this essential protein in human disease, and our findings suggest that TPR variants are the cause of the siblings' neurological disorder.